Mathematical communication ability viewing of self-efficacy in project-based learning assisted by performance assessment - Irta Ziyaadaturrizka; Rochmad Rochmad; Scholastika Mariani (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This research aims to achieve two primary objectives. Firstly, it seeks to assess the effectiveness of Project-Based Learning (PjBL) by incorporating performance assessment in enhancing students' mathematical communication abilities. Secondly, the study aims to characterize students' mathematical communication abilities to their self-efficacy levels. A mixed-methods approach was employed in this study, with a population comprising 251 seventh-grade students from SMP Negeri 24 Semarang. Data were gathered through mathematical communication skill tests, self-efficacy questionnaires, and interview guidelines. The experimental group underwent PjBL facilitated by performance assessment, while the control group experienced PjBL alone. Results indicated that the experimental group demonstrated classical mastery of mathematical communication abilities, with higher average and proportional achievements than the control group. PjBL assisted by performance assessment proved to be more effective than PjBL alone. Analysis of mathematical communication abilities based on students' self-efficacy levels revealed that (1) subjects with high self-efficacy fulfilled all indicators; (2) subjects with moderate self-efficacy fulfilled indicators one and two, were less proficient in fulfilling indicators four and were unable to fulfill indicator three; and (3) subjects with low self-efficacy fulfilled indicator one but had not yet achieved indicators two, three, and four.